Knowledge Surveys: An Effective and Robust Student Self-Assessment and Learning Tool - Sloan, Joel; Frank, Timothy; Scharff, Lauren; Becker, Karin (Teaching and Learning Inquiry, 2025)
Knowledge surveys (KS) are a student self-assessment tool consisting of an ability statement for each learning objective in a course. Students respond by rating their confidence in performing a specified skill. Pre-unit KS transparently communicate learning objectives, alert faculty to self-assessed knowledge and skills students possess as they enter a unit of instruction and support metacognitive learning through the unit’s lessons and activities. Post-unit KS allow comparison of student self-assessed learning with faculty assessments of student learning, providing feedback to support continued development of self-assessment skills, as well as metacognitive and self-regulated learning skills. This study synthesizes several semesters of KS implementation across six different engineering courses, taught by six instructors utilizing multiple assessment types (exams, technical writing, design projects) and delivery modes (in person, hybrid, online). Results indicate that student KS scores aligned with faculty assessments, and alignment improved with cycles of performance and feedback in a subset of courses with similar assessment types. Student feedback indicates value in KS as a learning guide and as a helpful addition to these courses for learning and self-assessment, with student quotes demonstrating positive student learning practices and evidence of metacognitive thinking. Faculty find KS easily manageable; they also appreciate how KS help maximize alignment within their courses and provide additional data to support student learning. Knowledge surveys are thus an effective, robust, and relatively easy-to-implement method to systematically incorporate a self-assessment component into a variety of courses.